Massacre at Amritsar - Furneaux, Rupert (London George Allen & Unwin Ltd, 1963)
Recreates the story of the killing of 379 Indians and wounding of 1200 others by British troops on April 13, 1919 at Amritsar, India.
Include Maps, Bibliography and Index
Keywords: Amritsar Massacre, Amritsar, India, 1919 -- Dyer, R. E. H. -- (Reginald Edward Harry), -- 1864-1927 -- India 1919